Analisis Scarcity dan Urgency pada Keputusan Pembelian Konsumen Hanasui di Live Shopee - Dewi Sriwidari; Hasim Hasim (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study aims to determine whether the role of Scarcity and Urgency applied by the Hanasui brand in the marketing process on the Shopee live feature can influence consumer purchasing decisions. Furthermore, the researchers refer to Scarcity and Urgency as limited product stock and limited time for a discount. The researcher used the Heuristic Systematic theory to analyze the Scarcity and Urgency process in the Hanasui brand live streaming on the Shopee application, namely the Heuristic Systematic theory, a theory that explains how a person processes information obtained either heuristically (without thinking) or systematically (regularly and comprehensively). Where the method used is a qualitative method with a constructivist paradigm and a qualitative descriptive approach. Meanwhile, the data collection techniques used were non-participant observation and in-depth interviews with predetermined subjects, namely five women, who have used or purchased Hanasui products on the Shopee live feature. Therefore, the results of this study, namely the Hanasui live feature on Shopee, show that Scarcity and Urgency play a role in consumer purchasing decisions.